Credible vertical preemption - Siebert, Ralph (online, 1999)
Abstract:
urn:nbn:de:0168-ssoar-194763
Keywords: (stw)Innovationswettbewerb; (stw)Innovation; (stw)Markteintritt; (stw)Duopol; (stw)Produktqualität; (stw)Verdrängungswettbewerb; (stw)Theorie; (thesoz)Produkt; (thesoz)Innovation; (thesoz)Angebot; (thesoz)Unternehmenspolitik; (thesoz)Nachfrage; (thesoz)Strategie; (thesoz)Unternehmen; (thesoz)Marktanteil; (thesoz)ökonomisches Modell; (thesoz)Preis; (thesoz)Markterschließung; (thesoz)Wettbewerb; (thesoz)Qualität; (thesoz)Glaubwürdigkeit; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Innovationswettbewerb; Innovation; Markteintrittsstrategie; Dyopol; Qualität; Verdrängungswettbewerb; Theorie